Arthroscopic subtalar arthrodesis through the sinus tarsi portal approach: A series of 77 cases. Issue 5 (October 2018) - Walter, R.P.; Walker, R.W.; Butler, M.; Parsons, S.
Highlights: The two portal sinus tarsi approach allows access to all three facets of the subtalar joint for arthrodesis. Arthroscopic subtalar arthrodesis minimises soft tissue envelope damage to improve recovery, union and complication rates. This approach can also be used to perform triple fusion and resection of hindfoot coalitions. Abstract: Background: Subtalar arthrodesis through an open approach carries significant risk of complications. An arthroscopic approach aims to minimise damage to the soft tissue envelope to improve recovery, union and complication rates. A two portal approach through the sinus tarsi was used. Methods: A retrospective review of all patients undergoing isolated arthroscopic arthrodesis was performed. Results: Seventy-seven procedures were performed. Successful arthrodesis was achieved in 75 (97.4%). Two patients underwent successful revision arthrodesis for aseptic nonunion. There was one (1.3%) superficial infection and one (1.3%) partial sural nerve injury. Conclusions: Two-portal sinus tarsi arthroscopic subtalar arthrodesis is safe and effective. Advantages over other arthroscopic approaches are the access to all three facets of the joint, avoidance of a posterolateral portal in order to minimise risk to the sural nerve, and the ability to use the same approach to arthrodese the entire triple hindfoot joint complex. Technical tips and pitfalls are discussed.